Chemical analyses of the essential oils from Varronia curassavica accessions in two seasons. Issue 6 (1st November 2020) - Oliveira, Bruna Maria Santos De; Blank, Arie Fitzgerald; Nizio, Daniela Aparecida De Castro; Nogueira, Paulo Cesar De Lima; Arrigoni-Blank, Maria De Fátima; Bacci, Leandro; Melo, Carlisson Ramos; Nascimento, Luís Fernando De Andrade; Sampaio, Taís Santos
ABSTRACT: This work aimed to analyze the chemical composition of the essential oils of Varronia curassavica accessions that were collected during the rainy (July 2015) and dry (January 2016) seasons. The essential oils were extracted by hydrodistillation and analyzed by GC/MS/FID. Fifty compounds were detected in the essential oils. The cluster analysis formed seven chemical clusters in the two harvest seasons. Only the accessions VCUR-302 and VCUR-502 presented major alterations in the chemical composition of their essential oil. These two accessions migrated from cluster 5 in the rainy season to cluster 6 in the dry season. Accession VCUR-105 had higher essential oil content in the rainy season (3.20%). Meanwhile, in the dry season, the accessions VCUR-003 (2.78%) and VCUR-101 (2.73%) were also productive, as well as VCUR-105 (2.84%). The bioactive compounds α-humulene and ( E )-caryophyllene were detected in all of the accessions of their essential oils in both seasons.